Perancangan Aplikasi Presensi Siswa Berbasis Website di SMK Negeri 1 Tengaran Menggunakan Webcam dan GPS Guna Mengurangi Risiko Penularan Virus COVID-19 - Juzack Kristiadhy; Adriyanto Juliastomo Gundo (Peneliti.net, 2022)
The presence of students is very important in learning activities at school. Attendance is a system used by educational institutions to determine the presence of a student at school. During the COVID-19 pandemic, attendance activities at schools, especially at SMK Negeri 1 Tengaran, were still using conventional methods. The essence of this research is to design an attendance application that can reduce the risk of COVID-19 transmission or reduce physical contact between students by updating the conventional attendance systematic flow. The design of this application uses the prototype design method and for feasibility testing uses the ISO 9126 standard. It is hoped that this application meets the feasibility test standard so that it can be used at SMK Negeri 1 Tengaran in order to reduce the risk of transmission of the COVID-19 virus. The participants of this study were students, homeroom teachers, counseling guidance teachers, and software engineers. The results of this feasibility test show that all aspects of the ISO 9126 standard tested including functionability, reliability, usability, efficiency, maintability, and portability indicate the category is very feasible to use or has passed the feasibility test according to the ISO 9126 standard.